Improved pinch-based method to calculate the capital cost target of heat exchanger network via evolving the spaghetti structure towards low-cost matching. (1st April 2022) - Fu, Dianliang; Nguyen, Truong; Lai, Yanhua; Lin, Leteng; Dong, Zhen; Lyu, Mingxin
Abstract: Ahead of heat exchanger network (HEN) design, setting an optimal pinch temperature difference for pinch analysis depends vitally on the capital cost target. Conventional methods based on the spaghetti (SPA) structure ignoring matching optimization might result in calculated cost targets of large deviations. This work evolved the SPA structure via four stages by shifting energy towards low-cost matching. The fourth structure evolved from the SPA structure (ESPA-IV structure) with the lowest-cost matching after loops elimination forms the base to establish the ESPA method. It is validated by numerical experiment and applied to a case reported in literature, meanwhile comparisons are always made to the SPA method. The numerical experiment proves that the ESPA method can obtain capital cost targets with higher accuracy than the SPA method. The target deviations (often within ±5%) given by the ESPA method are much lower than those (well above 10%) derived by the SPA method. In the case study, the given HEN is further optimized as hinted by ESPA method results. Of two target methods, the cost target indicated by ESPA method is closer to the optimum capital cost newly derived after optimization. The high accuracy of the ESPA method is further verified. Highlights: New method is proposed for the capital cost target of heat exchanger network (HEN). Lower-cost matching structures are evolved from the spaghetti structure (ESPA). Both numerical experiment and case study confirmed the reliability of ESPA method. ESPA method can work as a capital cost assessment tool to guide a HEN design.